Application of warp painting technique to produce 'ikat' effects - Mary Esther, anak Steel, (Universiti Malaysia Sarawak (UNIMAS), 2014)
Warp painting technique can produced effect similar to 'ikat' technique effect. This research focuses on creating 'ikat' effect by using wrap painting technique. The objective of this research is to experiment paintingon the warp threads. Various experiments were carried out to identify suitable threads to be. At the end of the experiment, a collection of 'ikat' effect fabric are produced and the products produce were validated to obtain feedback from consumers. The result show that warp painting technique has the potential to reduce weaving time to produce 'ikat' effect woven fabric.